Mineral fertilizers with recycled manure boost crop yield and P balance in a long-term field trial - Ning, Chuanchuan; Ma, Qiang; Yuan, Haiyan; Zhou, Changrui; Xia, Zhuqing; Yu, Wantai (Nutrient cycling in agroecosystems, 2020)
Crop uptake and neglecting to apply phosphate (P) fertilizer are important reasons for P deficit in the agro-ecosystem. Recycled manure from within the system was adopted to evaluate the effects of mineral fertilizer combined with or without manure on crop yield, P budget, and P use efficiency in a continuous 20-year field trial. The experiment contained eight treatments: no fertilizer, manure (M), N fertilizer (N), N fertilizer with manure (N + M), N and P fertilizers (NP), NP fertilizers with manure (NP + M), N, P, and K fertilizers (NPK), and NPK fertilizers with manure (NPK + M). The yield and P uptake of soybean and maize increased with the sequential supplement of N, P, and K fertilizers. Application of recycled manure not only increased the yield and P uptake of crops but also reduced the inter-annual fluctuations in soybean yield. Although application of mineral P fertilizer was the main method to preserve P budget surplus and increase soil available P, recycled manure could be a positive supplement. The proportion of residual fertilizer P converted to soil available P under NP, NP + M, NPK, and NPK + M treatments was 9%, 7%, 3%, and 8%, respectively over a 20-year period. Moreover, P use efficiency in NP and NPK treatments gradually increased first and then stabilized at around 20%, but the value was obviously lower than that from manure. The results clearly demonstrated that integrated application of mineral NPK fertilizers and recycled manure was a useful method to improve crop yield and soil P fertility.